A method for using a new type of lubricant resistant to low temperature and water
By using new lubricants with polyα-olefins and other components on the fasteners and galvanized passivation film technology, the problem of lubricants failure in low temperatures and water is solved, and the effective lubrication and service life of the fasteners in high-altitude areas is achieved. extend.
Patent Information
- Application Number
- CN202410665180.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-27
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-05-27
AI Technical Summary
The existing fastener lubricant fails in low temperatures and water, resulting in difficulty in disassembling fasteners and affecting the maintenance and repair of equipment.
A new lubricant including polyα-olefins, polydimethylsiloxane, molybdenum disulfide, fluorocarbon resin and polyether F68 is used, and fine concave points with uniform density are formed by galvanizing and light sandblasting treatment. Structure, improve the adhesion and lubricating effect of lubricant.
The lubricant maintains excellent resistance in low temperatures and water, extends the service life of the fastener and is effectively lubricated in harsh environments in high and cold areas, avoiding the problem of fastener failure due to environmental changes.
Smart Images

Figure SMS_3 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lubricants for fasteners, and in particular relates to a method for using a new type of lubricant that is resistant to low temperatures and water. Background Art
[0002] The lubricants currently on the market for adjusting the friction coefficient of fasteners such as bolts and nuts can meet the use requirements under normal temperature conditions. However, for fasteners used in rail transit, which mainly include bolts, screws, nuts and studs, they are in harsh outdoor environments in high-cold areas all year round. The lubricants of the fasteners often fail due to low temperatures and water immersion, resulting in tightness or biting, making it difficult to disassemble the fasteners and seriously affecting the maintenance and repair of the equipment. Therefore, a new type of lubricant that is resistant to low temperatures and water is urgently needed. Summary of the invention
[0003] Based on the content in the background technology, the present invention discloses a new type of low-temperature and water-resistant lubricant, which includes the following components in percentage by mass: 30-35% of polyalphaolefin, 25-29% of polydimethylsiloxane, 7-12% of molybdenum disulfide, 4-8% of fluorocarbon resin, 9-15% of polyether F68 and less than 1% of methyl silicone oil.
[0004] Preferably, the polyalphaolefin is purchased from SpectraSyn Elite™ metallocene polyalphaolefin of ExxonMobil Chemical, and the particle size of the molybdenum disulfide is 0.7 μm-1.5 μm.
[0005] Also disclosed is a method for using a new type of low-temperature-resistant and water-resistant lubricant, which comprises the following steps:
[0006] S1. The surface of the M36*240 bolt and nut fastener is galvanized, and the thickness of the galvanized layer is 35-55um. The specific galvanizing method is the prior art and will not be described here;
[0007] S2. The galvanized layer of the fastener is lightly sandblasted to form a fine pit structure with uniform density on the surface of the galvanized layer, and then washed and placed in a passivation solution for passivation treatment, wherein the passivation solution comprises the following components: 30-40 g / L of chromium nitrate, 23-30 g / L of sodium nitrate, 1-4 g / L of sulfonate, and 3-7 g / L of sodium nitrite;
[0008] S3. After the fasteners that have been passivated in step S2 are cleaned and dried to remove the water film on the surface, the above-mentioned new low-temperature-resistant and water-resistant lubricant is applied to the fastening joints of the fasteners.
[0009] The sulfonate in the above passivation solution is specifically sodium α-olefin sulfonate, which is used in the passivation solution to promote passivation. More importantly, it can improve the wettability and permeability of the passivation solution and the surface of the galvanized layer, so that the passivation solution can also completely infiltrate the fine pits on the surface of the galvanized layer, so that the concave surface of the pits can also be completely in contact with the passivation solution for passivation; sodium nitrate has a buffering effect in the passivation process, which can inhibit the oxidation reaction and avoid the formation of unnecessary oxides, and is conducive to the slow formation of a uniform passivation film at the fine pits on the surface of the galvanized layer, thereby enhancing the adhesion of the passivation film there, so that it can be more evenly covered on the concave surface of the pits;
[0010] In this way, with the cooperation of sulfonate and sodium nitrite in the passivation solution, a high-quality passivation film can also be formed on the fine pits on the surface of the galvanized layer. That is, through the above method, the passivation film formed on the galvanized layer of the fastener also has a fine pit structure with uniform density without affecting its film quality. These pits of the galvanized passivation film can not only improve the adhesion of the passivation film, but more importantly, increase the surface area of the passivation film, which is helpful to better absorb and store lubricants, thereby improving the adhesion and lubrication effect of the lubricant.
[0011] Among the components of the above lubricant, poly-α-olefin and polydimethylsiloxane are the basic components, and molybdenum disulfide is the solid powder component in the lubricant, which has high stability, natural hydrophobicity and low temperature resistance; fluorocarbon resin also has good chemical stability, low friction coefficient and cold resistance. In the lubricant, fluorocarbon resin has a certain "compatibility" with the galvanized passivation film of the fastener, which can make the lubricant component better attached to the galvanized passivation film; polyether F68 can be used to adjust the viscosity of the lubricant to improve the lubricating properties of the lubricant, which helps to form a uniform lubricating film, and can make the lubricant penetrate into the fine pits on the surface of the galvanized passivation film, which can ensure that the lubricant component can effectively contact and penetrate with the galvanized passivation film of the fastener, and improve the lubrication effect. Under the coordinated action of these lubricating components, the lubricant of the present application can play the best lubricating effect with the galvanized passivation film of the fastener, extending the service life of the fastener.
[0012] Preferably, in step S2: the light sandblasting selects 60-80 mesh alumina particles as the sandblasting particles, the speed of the sandblasting particles is controlled at 3-5m / s, compressed air can be selected as the power, and the light sandblasting time is 5-11s; such light sandblasting treatment can form a fine pit structure on the surface of the galvanized layer of the fastener without completely destroying the galvanized layer.
[0013] Furthermore, in step S2: the passivation solution also includes the following additives: 15-25 g / L citric acid, 2-5 g / L cerium sulfate, 5-10 g / L cobalt sulfate, the temperature of the passivation solution is controlled between 25-45°C, the pH value is controlled between 1.5-2.7 by sodium hydroxide, and the fastener is immersed in the passivation solution for 3-8 minutes.
[0014] Through the above technical solution, the present invention at least includes the following beneficial effects:
[0015] The novel lubricant of the present invention has excellent water resistance and low temperature resistance. When used in conjunction with the method for using the novel lubricant, the galvanized passivation film on the surface of the fastener has a fine pit structure with uniform density. The novel lubricant can exert the best lubrication coordination effect with the galvanized passivation film of the fastener, thereby extending the service life of the fastener. DETAILED DESCRIPTION
[0016] The technical solution of the invention will be clearly and completely described below through embodiments, and the application of the present invention is not limited to the embodiments given.
[0017] Example 1
[0018] A new type of low-temperature and water-resistant lubricant, comprising the following components in percentage by mass: 33% polyalphaolefin, 27% polydimethylsiloxane, 9% molybdenum disulfide, 7% fluorocarbon resin, 13% polyether F68 and 0.7% methyl silicone oil; the polyalphaolefin is purchased from SpectraSyn Elite™ metallocene polyalphaolefin of ExxonMobil Chemical, and the particle size of the molybdenum disulfide is 1.0 μm.
[0019] The method for using the new low-temperature and water-resistant lubricant is as follows, comprising the following steps:
[0020] S1. The surface of the M36*240 bolt and nut connection fastener is galvanized, and the thickness of the galvanized layer is 45um. The specific galvanizing method is the existing technology and will not be repeated here.
[0021] S2. The galvanized layer of the fastener is lightly sandblasted to form a fine pit structure with uniform density on the surface of the galvanized layer. The light sandblasting uses 70-mesh aluminum oxide particles as the blasting particles, the speed of the blasting particles is controlled at 4m / s, compressed air is selected as the power, and the light sandblasting time is 8s. Such light sandblasting can form a fine pit structure on the surface of the galvanized layer of the fastener without completely destroying the galvanized layer.
[0022] After being sandblasted and cleaned, the fasteners are placed in a passivation solution for passivation treatment. The passivation solution includes the following ingredients: 35 g / L chromium nitrate, 26 g / L sodium nitrate, 2.5 g / L sulfonate, 5 g / L sodium nitrite, 20 g / L citric acid, 4 g / L cerium sulfate and 7 g / L cobalt sulfate; the temperature of the passivation solution is controlled between 35°C, the pH value is controlled at 2.1 by sodium hydroxide, and the fasteners are immersed in the passivation solution for 5 minutes.
[0023] S3. After the fasteners that have been passivated in step S2 are cleaned and dried to remove the water film on the surface, the above-mentioned new low-temperature-resistant and water-resistant lubricant is applied to the fastening joints of the fasteners.
[0024] The sulfonate in the above passivation solution is specifically sodium α-olefin sulfonate, which is used in the passivation solution to promote passivation. More importantly, it can improve the wettability and permeability of the passivation solution and the surface of the galvanized layer, so that the passivation solution can also completely infiltrate the fine pits on the surface of the galvanized layer, so that the concave surface of the pits can also be completely in contact with the passivation solution for passivation; sodium nitrate has a buffering effect in the passivation process, which can inhibit the oxidation reaction and avoid the formation of unnecessary oxides, and is conducive to the slow formation of a uniform passivation film at the fine pits on the surface of the galvanized layer, thereby enhancing the adhesion of the passivation film there, so that it can be more evenly covered on the concave surface of the pits;
[0025] In this way, with the cooperation of sulfonate and sodium nitrite in the passivation solution, a high-quality passivation film can also be formed on the fine pits on the surface of the galvanized layer. That is, through the above method, the passivation film formed on the galvanized layer of the fastener also has a fine pit structure with uniform density without affecting its film quality. These pits of the galvanized passivation film can not only improve the adhesion of the passivation film, but more importantly, increase the surface area of the passivation film, which is helpful to better absorb and store lubricants, thereby improving the adhesion and lubrication effect of the lubricant.
[0026] Among the components of the above lubricant, poly-α-olefin and polydimethylsiloxane are the basic components, and molybdenum disulfide is the solid powder component in the lubricant. They have high stability, natural hydrophobicity and low temperature resistance; fluorocarbon resin also has good chemical stability, low friction coefficient and cold resistance. In the lubricant, fluorocarbon resin has a certain "compatibility" with the galvanized passivation film of the fastener, which can make the lubricant component better attached to the galvanized passivation film; polyether F68 can be used to adjust the viscosity of the lubricant to improve the lubricating properties of the lubricant, help to form a uniform lubricating film, and enable the lubricant to penetrate into the fine pits on the surface of the galvanized passivation film, which can ensure that the lubricant component can effectively contact and penetrate with the galvanized passivation film of the fastener, and improve the lubrication effect. Under the coordination of these lubricating components, the lubricant of the present application can play the best lubrication coordination effect with the galvanized passivation film of the fastener, extending the service life of the fastener.
[0027] The bolt-nut connection fastener coated with lubricant was divided into three samples, sample 1 was not treated in any way, sample 2 was placed in a -40°C environment for 2 hours, and sample 3 was immersed in water for 48 hours; then their torque coefficients k were measured on an LS-500B bolt torque tester. The results are shown in Table 1, which are the average values of multiple tests.
[0028] Example 2
[0029] A new type of low-temperature and water-resistant lubricant, comprising the following components in percentage by mass: 35% polyalphaolefin, 25% polydimethylsiloxane, 7% molybdenum disulfide, 8% fluorocarbon resin, 9% polyether F68, and 1% methyl silicone oil; the polyalphaolefin is purchased from SpectraSyn Elite™ metallocene polyalphaolefin of ExxonMobil Chemical, and the particle size of the molybdenum disulfide is 1.5 μm.
[0030] The method for using the new low-temperature and water-resistant lubricant is as follows, comprising the following steps:
[0031] S1. The surface of the M36*240 bolt and nut connection fastener is galvanized, and the thickness of the galvanized layer is 55um. The specific galvanizing method is prior art and will not be described in detail here.
[0032] S2. The galvanized layer of the fastener is lightly sandblasted to form a fine pit structure with uniform density on the surface of the galvanized layer. The light sandblasting uses 80-mesh aluminum oxide particles as the blasting particles, the speed of the blasting particles is controlled at 5m / s, compressed air is selected as the power, and the light sandblasting time is 10s. Such light sandblasting can form a fine pit structure on the surface of the galvanized layer of the fastener without completely destroying the galvanized layer.
[0033] After sandblasting and cleaning, the fasteners are placed in a passivation solution for passivation treatment. The passivation solution includes the following components: 30 g / L chromium nitrate, 23 g / L sodium nitrate, 4 g / L sulfonate, 7 g / L sodium nitrite, 25 g / L citric acid, 5 g / L cerium sulfate and 5 g / L cobalt sulfate; the temperature of the passivation solution is controlled between 25°C, the pH value is controlled at 2.7 by sodium hydroxide, and the fasteners are immersed in the passivation solution for 8 minutes.
[0034] S3. After the fasteners that have been passivated in step S2 are cleaned and dried to remove the water film on the surface, the above-mentioned new low-temperature-resistant and water-resistant lubricant is applied to the fastening joints of the fasteners.
[0035] The sulfonate in the above passivation solution is specifically sodium α-olefin sulfonate, which is used in the passivation solution to promote passivation. More importantly, it can improve the wettability and permeability of the passivation solution and the surface of the galvanized layer, so that the passivation solution can also completely infiltrate the fine pits on the surface of the galvanized layer, so that the concave surface of the pits can also be completely in contact with the passivation solution for passivation; sodium nitrate has a buffering effect in the passivation process, which can inhibit the oxidation reaction and avoid the formation of unnecessary oxides, and is conducive to the slow formation of a uniform passivation film at the fine pits on the surface of the galvanized layer, thereby enhancing the adhesion of the passivation film there, so that it can be more evenly covered on the concave surface of the pits;
[0036] In this way, with the cooperation of sulfonate and sodium nitrite in the passivation solution, a high-quality passivation film can also be formed on the fine pits on the surface of the galvanized layer. That is, through the above method, the passivation film formed on the galvanized layer of the fastener also has a fine pit structure with uniform density without affecting its film quality. These pits of the galvanized passivation film can not only improve the adhesion of the passivation film, but more importantly, increase the surface area of the passivation film, which is helpful to better absorb and store lubricants, thereby improving the adhesion and lubrication effect of the lubricant.
[0037] Among the components of the above lubricant, poly-α-olefin and polydimethylsiloxane are the basic components, and molybdenum disulfide is the solid powder component in the lubricant. They have high stability, natural hydrophobicity and low temperature resistance; fluorocarbon resin also has good chemical stability, low friction coefficient and cold resistance. In the lubricant, fluorocarbon resin has a certain "compatibility" with the galvanized passivation film of the fastener, which can make the lubricant component better attached to the galvanized passivation film; polyether F68 can be used to adjust the viscosity of the lubricant to improve the lubricating properties of the lubricant, help to form a uniform lubricating film, and enable the lubricant to penetrate into the fine pits on the surface of the galvanized passivation film, which can ensure that the lubricant component can effectively contact and penetrate with the galvanized passivation film of the fastener, and improve the lubrication effect. Under the coordination of these lubricating components, the lubricant of the present application can play the best lubrication coordination effect with the galvanized passivation film of the fastener, extending the service life of the fastener.
[0038] The bolt-nut connection fastener coated with lubricant was divided into three samples, sample 1 was not treated in any way, sample 2 was placed in a -40°C environment for 2 hours, and sample 3 was immersed in water for 48 hours; then their torque coefficients k were measured on an LS-500B bolt torque tester. The results are shown in Table 1, which are the average values of multiple tests.
[0039] Example 3
[0040] A new type of low-temperature and water-resistant lubricant, comprising the following components in percentage by mass: 30% polyalphaolefin, 29% polydimethylsiloxane, 12% molybdenum disulfide, 4% fluorocarbon resin, 15% polyether F68 and 0.3% methyl silicone oil; the polyalphaolefin is purchased from ExxonMobil Chemical's SpectraSyn Elite™ metallocene polyalphaolefin, and the particle size of the molybdenum disulfide is 0.7 μm.
[0041] The method for using the new low-temperature and water-resistant lubricant is as follows, comprising the following steps:
[0042] S1. The surface of the M36*240 bolt and nut connection fastener is galvanized, and the thickness of the galvanized layer is 35um. The specific galvanizing method is the existing technology and will not be repeated here.
[0043] S2. The galvanized layer of the fastener is lightly sandblasted to form a fine pit structure with uniform density on the surface of the galvanized layer. The light sandblasting uses 60-mesh aluminum oxide particles as the blasting particles, the speed of the blasting particles is controlled at 3m / s, compressed air is selected as the power, and the light sandblasting time is 5s. Such light sandblasting can form a fine pit structure on the surface of the galvanized layer of the fastener without completely destroying the galvanized layer.
[0044] After being sandblasted and cleaned, the fasteners are placed in a passivation solution for passivation treatment. The passivation solution includes the following components: 40 g / L chromium nitrate, 30 g / L sodium nitrate, 1 g / L sulfonate, 3 g / L sodium nitrite, 15 g / L citric acid, 2 g / L cerium sulfate and 10 g / L cobalt sulfate; the temperature of the passivation solution is controlled between 45°C, the pH value is controlled at 1.5 by sodium hydroxide, and the fasteners are immersed in the passivation solution for 3 minutes.
[0045] S3. After the fasteners that have been passivated in step S2 are cleaned and dried to remove the water film on the surface, the above-mentioned new low-temperature-resistant and water-resistant lubricant is applied to the fastening joints of the fasteners.
[0046] The sulfonate in the above passivation solution is specifically sodium α-olefin sulfonate, which is used in the passivation solution to promote passivation. More importantly, it can improve the wettability and permeability of the passivation solution and the surface of the galvanized layer, so that the passivation solution can also completely infiltrate the fine pits on the surface of the galvanized layer, so that the concave surface of the pits can also be completely in contact with the passivation solution for passivation; sodium nitrate has a buffering effect in the passivation process, which can inhibit the oxidation reaction and avoid the formation of unnecessary oxides, and is conducive to the slow formation of a uniform passivation film at the fine pits on the surface of the galvanized layer, thereby enhancing the adhesion of the passivation film there, so that it can be more evenly covered on the concave surface of the pits;
[0047] In this way, with the cooperation of sulfonate and sodium nitrite in the passivation solution, a high-quality passivation film can also be formed on the fine pits on the surface of the galvanized layer. That is, through the above method, the passivation film formed on the galvanized layer of the fastener also has a fine pit structure with uniform density without affecting its film quality. These pits of the galvanized passivation film can not only improve the adhesion of the passivation film, but more importantly, increase the surface area of the passivation film, which is helpful to better absorb and store lubricants, thereby improving the adhesion and lubrication effect of the lubricant.
[0048] Among the components of the above lubricant, poly-α-olefin and polydimethylsiloxane are the basic components, and molybdenum disulfide is the solid powder component in the lubricant. They have high stability, natural hydrophobicity and low temperature resistance; fluorocarbon resin also has good chemical stability, low friction coefficient and cold resistance. In the lubricant, fluorocarbon resin has a certain "compatibility" with the galvanized passivation film of the fastener, which can make the lubricant component better attached to the galvanized passivation film; polyether F68 can be used to adjust the viscosity of the lubricant to improve the lubricating properties of the lubricant, help to form a uniform lubricating film, and enable the lubricant to penetrate into the fine pits on the surface of the galvanized passivation film, which can ensure that the lubricant component can effectively contact and penetrate with the galvanized passivation film of the fastener, and improve the lubrication effect. Under the coordination of these lubricating components, the lubricant of the present application can play the best lubrication coordination effect with the galvanized passivation film of the fastener, extending the service life of the fastener.
[0049] The bolt-nut connection fastener coated with lubricant was divided into three samples, sample 1 was not treated in any way, sample 2 was placed in a -40°C environment for 2 hours, and sample 3 was immersed in water for 48 hours; then their torque coefficients k were measured on an LS-500B bolt torque tester. The results are shown in Table 1, which are the average values of multiple tests.
[0050] Table 1:
[0051]
[0052] It can be seen from the above table that the lubricant of the present invention, when used in combination with its method of use, still has a good lubricating effect after being exposed to -40°C for 2 hours and immersed in water for 48 hours. The lubricant on the surface of the fastener will not become ineffective due to environmental changes. It has excellent low-temperature resistance and water resistance, and the product meets the requirements of outdoor use environments in high-cold areas.
[0053] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Based on the present invention and the above description, relevant personnel can make various changes and modifications without departing from the technical idea of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for using a new type of lubricant that is resistant to low temperatures and water, characterized in that: The following steps are involved: S1. Galvanize the surface of the fastener, and the thickness of the zinc coating is 35-55um; S2. The galvanized layer of the fastener is lightly sandblasted to form a fine pit structure with uniform density on the surface of the galvanized layer, and then washed and placed in a passivation solution for passivation treatment, wherein the passivation solution comprises the following components: 30-40 g / L of chromium nitrate, 23-30 g / L of sodium nitrate, 1-4 g / L of sulfonate and 3-7 g / L of sodium nitrite; S3. After the fasteners that have been passivated in step S2 are washed and dried to remove the water film on the surface, a new low-temperature and water-resistant lubricant is applied to the fastening joints of the fasteners; the new low-temperature and water-resistant lubricant includes the following components in percentage by mass: 30-35% of polyalphaolefin, 25-29% of polydimethylsiloxane, 7-12% of molybdenum disulfide, 4-8% of fluorocarbon resin and 9-15% of polyether F68.
2. The method for using the new low-temperature-resistant and water-resistant lubricant according to claim 1, characterized in that: The particle size of the molybdenum disulfide is 0.7-1.5 μm.
3. The method for using a new type of low temperature resistant and water resistant lubricant according to claim 1 or 2, characterized in that: In step S2: the light sandblasting uses 60-80 mesh aluminum oxide particles as sandblasting particles, the speed of the sandblasting particles is controlled at 3-5 m / s, and the light sandblasting time is 5-11 s.
4. The method for using a new type of low temperature resistant and water resistant lubricant according to claim 1 or 2, characterized in that: In step S2: the passivation solution also includes the following additives: 15-25g / L citric acid, 2-5g / L cerium sulfate and 5-10g / L cobalt sulfate. The temperature of the passivation solution is controlled between 25-45°C, the pH value is controlled between 1.5-2.7 by adjusting the amount of sodium hydroxide added, and the fastener is immersed in the passivation solution for 3-8min.
Citation Information
Patent Citations
Threaded connection for pipes or tubes and method for producing the threaded connection for pipes or tubes
CA3064359A1
Antifriction coatings, methods of producing such coatings and articles including such coatings
CN101426590A